CHARACTERISTICS OF RAW PROCESSING OF "UZBEKISTAN-83" AND "HOSILDOR" VARIETIES (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
Beetroot is one of the main nutritious root vegetables. Hashaki beet is one of the foods rich in carbohydrates and its content is 92.2 g of fiber and 60.5 g of ash residue. Hashaki beet is very important in increasing the milk yield of dairy cows. Beetroot is one of the juicy and easily digestible foods and accelerates the digestion of coarse foods. Beetroot makes up 40-50% of the ration of dairy cows in the livestock sector. As a repeated crop, planting Uzbek Nimqand variety and Uzbekistan-83 variety in our republic is appropriate.